The calculation and comparison of integral dose for the rectum, bladder, right and left femur heads in two methods of prostate cancer radiotherapy: S.A.S IMRT vs. 3D CRT - Kaveh Shirani Tak Abi; Hassan Ali Nedaie; Hossein Hassani; Mansour Naderi; Mohammad Babaie; Mahmood Samei; Bahram Andalib; Saeideh Sakhaei; Nooshin Banaee (Basic & Clinical Cancer Research, 2014)
The aim of radiation therapy treatment planning is to achieve an optimal balance between delivering a high dose to target volume and a low dose to healthy tissues. In order to refrain any complications resulting from the dose to the surrounding normal organs, the role of treatment plan has been critically evaluated in term of how large the volume or mass of normal tissues exposed in the radiation. The integral dose, hence, is one of the important guidance for predicting the radiation effects and choosing the treatment plan. The goal of this study is to compare and investigate the integral doses in conformal 3D vs. IMRT plan. Dosimetric data from five patients of prostate cancer, treated by simultaneous integrated boost IMRT and 3D CRT were evaluated in this prospective study. Target volume and organs at risk were contoured using M.I.R.S Treatment Planning System (Module Integrated Radiotherapy System version 5.0.00). A dose of 80 Gy to the PTV1, 57 Gy to RTV2 and 62 Gy to the PTV3 and 70Gy in 3D CRT and for P V, was prescribed. For each patient IMRT plans using S.A.S (dynamic Step and Shoot) and 3D CRT with 6, 10 and 18MV energies, were done. To calculate the ID to the normal healthy tissue all the target volumes were achieved. The Integral Dose was calculated as the mean- dose times the volume of the structure. A total of thirty IMRT and 3D CRT plans were performed for evaluation. The mean ID received by rectum for 3D CRT was almost 1.04% greater than IMRT while in bladder mean value of ID for IMRT is also bigger than 3D CRT approximately about 1.04%. In RFH and LFH the mean values of ID for 3D CRT were almost 1.05% and 1.06% greater than IMRT, respectively. Due to the three PTVs in IMRT the integral dose in target volume has the biggest value comparing with 3D CRT, considerably.